(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
Ten pathogenic fungi of Deuteromycetes were isolated from seven angiospermic hosts such as pointed gourd, tomato, rice, wheat, maize, chickpea and jute. Morphological characterization and molecular analyses were performed for accurate identification of the isolated pathogenic fungi. The sequence results obtained using the ITS1 and ITS4 primers were compared with NCBI GenBank and BOL database using BLAST analysis. Fusarium chlamydosporum and Penicillium pinophilum are recorded first time from Bangladesh.